Advances in omalizumab treatment for IgE-mediated food allergies - Siqi WANG; Ling YE; Meiling JIN (Zhongguo Linchuang Yixue)
The increasing prevalence of food allergies significantly affects both the physical and mental health of patients, while concurrently imposing a substantial economic burden on a global scale. Immunoglobulin E (IgE)-mediated food allergies typically manifest as acute reactions and may lead to severe allergic responses. Previous treatment strategies have been predominantly centered on allergen avoidance and oral immunotherapy (OIT), resulting in augmented economic and psychological burdens. In recent years, omalizumab, the anti-IgE monoclonal antibody, has emerged as a treatment option, either as monotherapy or in combination with OIT, for patients with IgE-mediated food allergies. Omalizumab holds promise in augmenting allergen tolerance, accelerating desensitization processes, and mitigating adverse effects associated with OIT. Nonetheless, a multitude of unresolved inquiries persist concerning the practical applications of omalizumab, necessitating additional real world studies for clarification.